2023
DOI: 10.3389/fneur.2022.1094073
|View full text |Cite
|
Sign up to set email alerts
|

Hemilaminectomy for the removal of the spinal tumors: An analysis of 901 patients

Abstract: ObjectiveWe report our experience with the use of hemilaminectomy approach for the removal of benign intraspinal tumors.MethodA retrospective review of 1,067 patients who underwent hemilaminectomy in our hospital between 2013 and 2019 was analyzed. Baseline medical data were collected. One hundred sixteen patients were excluded due to degenerative diseases, spinal bone tumors, and malignant tumors. The remaining 901 patients (916 tumors) were enrolled. The Dennis Pain Scale (DPS) was used to assess improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Cutting the dentate ligament and rotation of operating table enable a better visualization of the tumor. 7,18 A case series by Onken et al demonstrated also similar EOR in anterior SM in comparison with dorsal ones, 8 unilateral hemilaminectomy can also be used in more difficult cases with calcified meningiomas. 42 This approach is much less invasive than alternative approaches to ventrally located meningiomas, as previously described.…”
Section: Surgical Approachmentioning
confidence: 87%
See 2 more Smart Citations
“…Cutting the dentate ligament and rotation of operating table enable a better visualization of the tumor. 7,18 A case series by Onken et al demonstrated also similar EOR in anterior SM in comparison with dorsal ones, 8 unilateral hemilaminectomy can also be used in more difficult cases with calcified meningiomas. 42 This approach is much less invasive than alternative approaches to ventrally located meningiomas, as previously described.…”
Section: Surgical Approachmentioning
confidence: 87%
“…Our results are in line with several previous studies. 6-8 In the past, one study has reported contrary results. 15 Goodarzi et al presented their findings, wherein they compared the 2 different approaches and observed a lower rate GTR when using a unilateral approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous publications comparing both approaches show significantly less blood loss and lower LOS [11]. More invasive surgical approaches do not seem to be required in most cases, even in ventral located and calcified meningiomas [11,27,39,40], and other intradural tumors [41]. Furthermore, minimal invasive unilateral approaches seem to play a role in preventing CSF leakage, one of the more frequent possible complications of after surgery on intra-dural pathologies [20,22,42,43].…”
Section: Minimal Invasive Surgerymentioning
confidence: 91%
“…With the development and popularity of minimally invasive neurosurgery, most intraspinal tumours can be removed through microforaminotomy [ 4 ] after piecemeal resection (removing the tumour in small pieces), which may increase the risk of tumour metastasis in some tumours, such as ependymomas. Ependymomas are prone to spread in the spinal canal during surgery [ 5 7 ], and the total laminectomy approach is preferred.…”
Section: Introductionmentioning
confidence: 99%